DIMINISHING RELIGIOUS EXTREMIST UNDERSTANDING: CONTEXTUALIZATION OF THE QURAN'S VERSES ABOUT KILLING IN SYAIKH NAWAWI AL-BANTANI 'S MARAH LABID - Muh Gufron Hidayatullah; Abu Bakar (Al'Adalah, 2022)
Understanding qital verses in language and context is crucial in correcting radical views. In understanding a verse about war or killing, it is essential always to consider the historical context and use an adequate linguistical analysis to avoid mistakes in concluding the meaning of said passages. If these two aspects are applied during the interpretation of qital verses, radicalized views will be able to be reduced. One of the interpretation books qualified as such is Nawawi al-Bantani's Marah Labid. There is a uniqueness within this interpretation that is interesting to study. This research used the qualitative model to understand qital verses and the contextualization in Marah Labid's interpretation. The method used for this research was normative research. The primary source of this research was the Marah Labid, which is the interpretation of Nawawi regarding qital verses. Data collection and analysis were done by searching and studying Syaikh Nawawi's interpretation of qital, then contextualizing them with recent times using Fazlul Rahman's theory. The result of this research underlined a few points; firstly, in almost every qital verse, Nawawi's interpretation began with the word ibtida', which means 'is started (by).' With this interpretation, it is understood that the qital verses are not orders to wage war against unbelievers without the existence or threat of attacks. On the contrary, these verses placed war as a means to retaliate against the unbelievers who have attacked first or are known to have plans to attack (kill). Secondly, the order to wage war must be interpreted with the context behind its reveal in mind; said condition should then be compared and correlated with recent times.